Hemophilia: a biography on therapeutical approaches - Catelli, Dayenne Helena; Plentz Portich, Júlia; Tabares Calvache, Ebellins; Seganfredo Weber, Cristiane; Sander Hoffmann, Daniel; Rasia Bosi, Guilherme; Sekine, Leo; da Rocha Silla, Lucia Mariano (Clinical and Biomedical Research, 2023)
The history of hemophilia is ancient, with descriptions dated to the 2nd century AD. The first modern narratives appeared in 1800s, when total blood transfusion was the only available treatment and life expectancy was remarkably low. Advances occurred with the use of plasma and cryoprecipitate, but only the discovered of factor concentrates revolutionized the treatment. The implantation of prophylaxis allowed hemophilic patients to prevent bleeding and the development of chronic arthropathy, although with a significant burdensome with the regular infusions. In the past 20 years, this field has witnessed major improvements, including the development of gene therapy and other pharmacological approaches.